Once upon an alphabet - Jeffers, Oliver (Philomel Books, an imprint of Penguin Group (USA), 2014)
"From an Astronaut who's afraid of heights, to a Bridge that ends up burned between friends, to a Cup stuck in a cupboard and longing for freedom, this series of interconnected stories and characters explores the alphabet"--